The captain of the men of death and his shadow: Long-run impacts of early life pneumonia exposure - Sonia R. Bhalotra; Atheendar Venkataramani (Institute for the Study of Labor (IZA), 2011)
We exploit the introduction of sulfa drugs in 1937 to identify the causal impact of exposure to pneumonia in infancy on later life well-being and productivity in the United States. Using census data from 1980-2000, we find that cohorts born after the introduction of sulfa experienced increases in schooling, income, and the probability of employment, and reductions in disability rates. These improvements were larger for those born in states with higher pre-intervention levels of pneumonia as these were the areas that benefited most from the availability of sulfa drugs. These estimates are, in general, larger and more robust to specification for men than for women. With the exception of cognitive disability and poverty for men, the estimates for African Americans are smaller and less precisely estimated than those for whites. This is despite our finding that African Americans experienced larger absolute reductions in pneumonia mortality after the arrival of sulfa. We suggest that pre-Civil Rights barriers may have inhibited their translating improved endowments into gains in education and employment.
urn:nbn:de:101:1-201110263858
Keywords: I18; H41; 330; early childhood; infectious diseases; pneumonia; medical innovation; antibiotics; schooling; income; disability; mortality trends; Infektionskrankheit; Kinder; Pharmazeutische Forschung; Pharmazeutisches Produkt; Lebensverlauf; Einkommen; Sterblichkeit; USA